Lucky breaks - Patron, Susan 1948- (Listening library, 2009)
Lucky makes a new friend, gets stuck in a well, meets up with a wild burro, discards something she didn't know was precious, and discovers the secret of the universe in this charming and funny sequel to the Newbery Award-winning The higher power of lucky